Assessment of the risk of falls and functional capacity in the elderly with knee osteoarthritis (Research, Society and Development, 2021)
Introduction: Osteoarthrosis is a chronic-degenerative disease, with high prevalence among the elderly, which causes pain, joint stiffness and decreased mobility, thus promoting functional incapacity and negative impact on quality of life. Objective: to assess the level of osteoarthritis in the knees, risk of falls and functionality in the elderly. Methods: Observational, descriptive, cross-sectional, quantitative study. The sample consisted of 16 elderly people aged over 60 years. Use the socioclinical questionnaire to check the profile of the population, the WOMAC, to assess the level of osteoarthritis in the knees; the Berg and Tinetti balance scales to assess balance and the risk of falls, and the Katz Index and Lawton and Brody Scale to assess functionality. Results: The population showed a predominance of women (81.3%), with a mean age of 68.44 ± 6.42 years and BMI of 28.97 ± 3.51 kg/m2. It was observed that by WOMAC, 37.5% showed little impairment by osteoarthrosis. In the Berg classification and Tinetti scale, 75.0% presented good balance and did not present a risk of falls. And both by the Katz scale and by the Lawton & Brody classification, the elderly were considered independent with the same percentage of 62.5%. Final Considerations: The study showed a moderate level of functional impairment due to osteoarthrosis, but with preserved balance, low risk of falls and preserved functional independence for both Basic Activities of Daily Living (BADLs) and Instrumental Activities of Daily Living (IADLs).